AnthropomorphicMeasurements and Event Free Survival in Patients with Favorable Histology Wilms Tumor: A Report from the Children’s Oncology Group - Fernandez, Conrad V. (2009)
PURPOSE: We retrospectively examined the effect of body weight and body mass index (BMI) on event-free survival (EFS) of children with Wilms tumor treated on National Wilms Tumor Study-5 (NWTS-5). PATIENTS AND METHODS: Eligible study participants: Stage I - IV favorable histology Wilms tumor with immediate nephrectomy; height and weight recorded at diagnosis, and loss of heterozygosity for chromosomes 1 p and 16 q assessed. RESULTS: A total of 1,532 patients were included in the analysis. The median follow-up was 4.9 years. 493 patients were less than 2 years of age and 1039 were 2 years of age or older. In both age groups there were more patients than expected with a weight or body-mass-index (BMI) less than the 10%ile or greater than the 90%ile. There was no relationship of weight-for-age or BMI-for-age and EFS in univariate analyses (p=0.28, log-rank test for both comparisons). A Cox proportional hazards model, stratified by risk/treatment groups, showed that, among patients less than 2 years of age, low or high weight-for-age was not predictive of EFS (p=0.16). Similarly, a Cox proportional hazards model, stratified by risk/treatment groups, showed that among patients greater than 2 years of age, low or high body mass index for age was not predictive of EFS (p=0.58). CONCLUSIONS: There was no evidence that anthropomorphic data obtained at diagnosis for patients with favorable histology stage I - V Wilms tumor was predictive for EFS in the setting of current treatment regimens. There were more patients with lower or higher weight/BMI than expected.